Novel pineapple leaf fibre composites coating with antimicrobial compound as a potential food packaging - Tatsaporn Todhanakasem; Sorawit Panjapiyakul; Piyawit Koombhongse (Packaging Technology and Science, 2021)
Abstract Biodegradable packaging coated with antimicrobial compounds has emerged as a new type of food packaging with potential to enhance food safety, extend shelf life and minimize plastic pollution. We have developed a polylactic acid (PLA) composite pineapple leaf fibre (PALF) biopolymer to fulfil the high demand of biodegradable materials for a potential use in food packaging. Our formulation with 10% pineapple fibre PLA/PALF composites exhibited enhanced melting temperatures and heat resistance, with a 44% reduction in the tensile strength and 2.7‐fold reduction on the strain at the break when compared with neat PLA. To impart antimicrobial activity, the PLA/PALF was coated with crude supernatants isolated from Pediococcus pentosaceus PP04 containing 1.3% w/v of nisin. This material coated with the crude extract was shown to inhibit the growth of Bacillus cereus ATCC 11778, Salmonella enterica subsp. enterica serovar Typhimurium ATCC 13311, and Escherichia coli ATCC 8739 in culture conditions, as well as minimizing the number of the tested pathogens on coated material surfaces.
Keywords: Nanocomposite Films for Food Packaging; Pineapple and bromelain studies; biodegradable polymer synthesis and properties